Hubungan Status Gizi, Pengetahuan, dan Suhu Tubuh dengan Asupan Cairan pada Ibu Hamil di Jakarta Barat - Husnul Mar'ah; Dodik Briawan; Ikeu Tanziha (Universitas Islam Negeri Walisongo Semarang, 2019)
This research has the aim to analyze the relationship of nutritional status, knowledge, body temperature with fluid intake in pregnant women in West Jakarta. This study design used a cross sectional approach, with number of subjects 84 pregnant women in West Jakarta. Sampling using a purposive sampling method. The nutritional status of pregnant women was obtained based on the weight record before pregnancy. Subject knowledge and fluid intake were obtained by interview with questionnaire. The subject's body temperature was measured with a digital thermometer. Analysis of the relationship between nutritional status, knowledge, and body temperature with fluid intake using the Spearman test. Based on the test of the relationship of nutritional status with fluid intake, the value of p = 0,002 was obtained. Analysis of the relationship of knowledge with fluid intake obtained p = 0,022 and the relationship between body temperature and fluid intake obtained p = 0,089. The conclusion that can be obtained is that there is a relationship between, nutritional status, knowledge with fluid intake, and body temperature has no relationship with fluid intake.